Efficacy of Elaeagnus angustifolia Topical Gel in the Treatment of Symptomatic Oral Lichen Planus - Jamileh Beigom Taheri; Fahimeh Anbari; Ziba Maleki; Shiva Boostani; Afshin Zarghi; Firoz Pouralibaba (Tabriz University of Medical Sciences, 2010)
Background and aims. The purpose of this study was to determine efficacy of 19% Elaeagnus angustifolia (EA) topical gel in the treatment of symptomatic oral lichen planus. Materials and methods. Patients with symptomatic oral lichen planus referring to the Department of Oral Medicine, Faculty of Dentistry at Shahid Beheshti University of Medical Sciences were asked to participate in the study. Twenty-eight patients who were histopathologically diagnosed with lichen planus were divided into two groups (15 in the case and 13 in the control groups). The subjects were randomly assigned to either topical gel of EA or placebo in a double-blind manner. They were then instructed to apply the medication on dried lesions three times daily. Pain and size of the lesions were evaluated after 2 weeks. Data were analyzed by SPSS 12.0 software, using t-test, paired t-test, Fisher's exact test and chi-square test. Results. Twenty-eight patients (m/f: 7/21) with symptomatic oral lichen planus participated in the study. Fifteen patients (m/f: 4/11) received E A gel and 13 patients (m/f: 3/10) received placebo. There was a 75% decrease in pain (33.3% in the case and 7.7% in the control groups), and a decrease of 50% in size (33.3% in the case group) and 75% only in 7.6% of the case group. Conclusion. The results suggest that 19% EA gel is efficient in the treatment of symptomatic oral lichen planus, with antiinflammatory and analgesic effects, as well.